Strategi Sosialisasi Dalam Rangka Meningkatkan Kepatuhan Wajib Pajak Orang Pribadi Di Masa Pandemi Covid-19 Pada KPP Pratama Jakarta Kelapagading Tahun 2021 - Putri Jernih Ndruru; Erni Prasetiyani (Jurnal Ilmu Administrasi Publik, 2023)
The lack of taxpayer compliance is influenced by things such as the lack of effective socialization from the government to call for paying taxes; lack of knowledge of taxpayers about taxes; There is also public concern that the collected tax revenue is not being used properly. This study aims to analyze the socialization strategy that will be carried out by the agencyto improve taxpayer tax compliance during the Covid-19 pandemic in Indonesia in Kantor Pelayanan Pajak Pratama Jakarta Kelapa Gading. Thisstudy uses a qualitative descriptive method by conducting interviews with informants. The data and information obtained were summarized, then analyzed using data reduction. The results of the analysis obtained several strategies including publications, activities, reporting, community involvement, inclusion of  identity  and personal  approach in conducting tax socialization. Implementation of the level of compliance of individual taxpayers on Kantor Pelayanan Pajak Pratama Jakarta Kelapa Gading he year 2019-2021 shows results that are not optimal, firstly because there are still many taxpayers who have not carried out their tax obligations and secondly, it can be seen from the compliance ratio in 2021 which experienced a decrease in the level of complianc .